2023
DOI: 10.3390/horticulturae9060711
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Physiobiochemical and Yield Characteristics of Pea Plants with Nano Silica and Melatonin under Salinity Stress Conditions

Wasimah B. Al-Shammari,
Haya R. Altamimi,
Khaled Abdelaal

Abstract: The effect of nano silica (50 mL L−1) and melatonin (75 µM) individually or in combination in foliar applications on the morphophysiological, biochemical and yield properties of pea plants under salinity stress conditions was evaluated. Salt stress caused a remarkable decrease in the growth and yield characteristics; for example, the plant dry weight, plant height, number of flowers plant−1, number of pods plant−1, weight of 100 green seeds and protein concentration in the pea plants during both seasons were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 82 publications
3
4
0
Order By: Relevance
“…In the presented study, salt stress significantly inhibited the seed germination and seedling growth of S. baicalensis , regardless of whether the seeds were primed or not. This is in agreement with the other studies that demonstrated negative effects of salt stress on plant growth [ 14 , 24 ]. PEG priming showed significantly enhanced seed germination rate and seedling growth of S. baicalensis under salt stress, certificating the positive role of seed priming in plant response to environmental stress.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the presented study, salt stress significantly inhibited the seed germination and seedling growth of S. baicalensis , regardless of whether the seeds were primed or not. This is in agreement with the other studies that demonstrated negative effects of salt stress on plant growth [ 14 , 24 ]. PEG priming showed significantly enhanced seed germination rate and seedling growth of S. baicalensis under salt stress, certificating the positive role of seed priming in plant response to environmental stress.…”
Section: Discussionsupporting
confidence: 93%
“…In the presented study, salt stress significantly inhibited the seed germination and seedling growth of S. baicalensis, regardless of whether the seeds were primed or not. This is in agreement with the other studies that demonstrated negative effects of salt stress on plant growth [14,24]. PEG…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, Ref. [40] reported a similar observation in S. hortensis under saline conditions. Consequently, gas exchange parameters decreased under saline conditions in our study.…”
Section: Discussionsupporting
confidence: 52%
“…The increase of hydrogen peroxide (H 2 O 2 ) and super oxide (O 2 ) under infection was observed. Enzymatic and non-enzymatic components such as Catalase (CAT), ascorbate peroxidase (APX), peroxidase (POX), polyphenol oxidase (PPO), ascorbic acid, glutathione, carotenoids, and proline are very important in plants' defense system against stress conditions [23,24]. CAT, POX, and PPO up-regulation play a critical role in protecting plants from pathogen attack and scavenge ROS as well as alterations in membrane permeability as a result of either biotic or abiotic stresses [25,26].…”
Section: Introductionmentioning
confidence: 99%